By-product of the wine industry for control of Meloidogyne javanica - Aparecida Reiner, Driéli; Dallemole-Giaretta, Rosangela; dos Santos, Idalmir; Afonso Ferreira, Paulo; Chiamulera Deifeld, Felipe Luiz; Antônio Lopes, Everaldo (Revista Mexicana de Ciencias Agrícolas, 2022)
Wine industry by-product (WIB) is rich in bioactive compounds, including phenolics. Since root-knot nematodes are suppressed by phenolic compounds, soil amendment with WIB may control these pathogens. We evaluated the effect of wine industry by-product (WIB) on the management of Meloidogyne javanica in tomato plants in greenhouse. In the first study, potted soil was amended with 0, 5, 10, 15, 20 25 and 30 g of WIB per kg of soil. Increasing doses of WIB increased plant development. Nematode population was reduced by WIB, especially at the dose of 30 g kg-1 of soil. In the second study, a split-root experiment was designed to assess if soil amendment with WIB (30 g kg-1 of soil) induces resistance on tomato against M. javanica. WIB does not induce tomato resistance against M. javanica. This residue controls the nematode by direct contact.